JURIDICAL REVIEW OF LAW NUMBER 12 OF 2022 CONCERNING CRIMINAL ACTS OF SEXUAL VIOLENCE IN ACCESSIBILITY OF JUSTICE FOR WOMEN - Apdila Wirawan, I Kadek; Permatasari, Pita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
This study aims to find out the substance of the breakthrough from the existence of Law Number 12 of 2022 concerning Crimes of Sexual Violence (“Law Number 12 of 2022”) and the accommodation of the Supreme Court Regulation of the Republic of Indonesia Number 3 of 2017 concerning Guidelines for Trialing Cases of Women Confronting the Law (“Supreme Court Regulation Number 3 of 2017”) related to the accessibility of justice for women as victims of criminal acts of violence sexual. The formulation of the problem taken is Law Number 12 of 2022 in obtaining accessibility to justice for women as victims and how can the Supreme Court Regulation Number 3 of 2017 concerning Guidelines for Trialing Cases of Women Confronting the Law accommodate women to gain accessibility justice in crimes of sexual violence. The results of this study are that in substance the protection of victims of sexual violence encourages material and formal changes in the formation of Law Number 12 of 2022. The change in the formal aspect is the development of criminal procedural law in the law on criminal acts of sexual violence, especially in terms of evidence. The development of evidence from witnesses such as the exception to the principle of unus testis nullus testis in Law Number 12 of 2022, the strength of evidence for the defendant's family as a witness. Matters that must be considered by judges in order to try and ensure that women dealing with the law obtain justice in crimes of sexual violence based on Supreme Court Regulation Number 3 of 2017, namely: (a) losses suffered by victims and compensation/restitution; (b) whether there is a power relation and the condition of the victim's powerlessness; (c) the impact of the case physically, psychologically, socially, economically; (d) there is a cycle of sexual violence, a history of sexual violence from the perpetrator to the victim; (e) the condition of women victims/witnesses; (f) Women's experiences related to sexual violence; (g) potential dangers that threaten the lives of women victims; (h) the need for recovery; and (i) results of post mortem et repertum and post mortem et repertum psychiatricum.